Attitudes in an interpersonal context: Psychological safety as a route to attitude change - Itzchakov, Guy; DeMarree, Kenneth G. (Frontiers in Psychology, 2022)
The interpersonal context can be complex: two or more people are interdependent, each pursuing individual and shared goals. The interaction consists of individual and joint behaviors dynamically interacting over time. Such interactions can potentially affect people’s attitudes. Indeed, the interpersonal context is one in which conversation partners have a great deal of opportunity to intentionally or even unintentionally influence one another. Yet, despite the importance of understanding attitudes and attitude change in interpersonal interactions, the topic has been understudied relative to other contexts of attitude change. Therefore, we briefly review the interpersonal context and build a case that understanding people’s sense of psychological safety is key to understanding interpersonal influences on people’s attitudes. Specifically, feeling psychologically safe can make individuals open-minded, increase reflective introspection, and decrease defensive processing. Such psychological safety impacts how individuals think, make sense of their social world, and process attitude-relevant information. These processes can result in attitude change, even without any persuasive attempt. The present paper aims to shed light on psychological safety as an essential avenue of interpersonal attitude change. To do so, we review relevant literature on interpersonal threats, receiving psychological safety, providing psychological safety, and interpersonal dynamics. Finally, we note limitations with the current approaches and unanswered questions and offer recommendations for future research that would contribute to developing this progressing research area.